Establishing Hydrographic Control Using Doppler - Minkel, David H. (The International Hydrographic Review, 2015)
Two Doppler Satellite surveys conducted for the purpose of establishing hydrographic control stations are reviewed. One survey was conducted in Monterey, Calif., the other established shore control for an upcoming hydrographic survey of Lake Superior to be performed by the National Ocean Service (NOS). A brief discussion of the positional accuracies obtained using relative positioning programs Magnet and Geodop V is included. The Lake Superior project is discussed regarding methods used and total cost incurred.